2012
DOI: 10.1021/mp300391v
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Distribution and Toxicity of PAMAM Dendrimers in the Central Nervous System Depend on Their Surface Chemistry

Abstract: Dendrimers have been described as one of the most tunable and therefore potentially applicable nanoparticles both for diagnostics and therapy. Recently, in order to realize drug delivery agents, most of the effort has been dedicated to the development of dendrimers that could internalize into the cells and target specific intracellular compartments in vitro and in vivo. Here, we describe cell internalization properties and diffusion of G4 and G4-C12 modified PAMAM dendrimers in primary neuronal cultures and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
114
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(117 citation statements)
references
References 27 publications
3
114
0
Order By: Relevance
“…22 The application of fluorescence imaging in living cells by confocal laser scanning microscopy and recently by two-photon imaging microscopy can monitor the dynamic aspects of cellular trafficking and colocalization of dendrimers with high spatial and temporal resolution. [23][24][25] The cellular internalization and trafficking of dendrimers depend on their size, shape, charge, and surface functionality as well as the cell type. 26,27 Many studies have revealed that cationic PAMAM dendrimers can cross cell membranes by various endocytic pathways, including clathrin-dependent pathways in Caco-2 cells, 28,29 clathrin-dependent and macropinocytosis pathways in HeLa cells, 30 and non-clathrin, non-caveolae, cholesterol-dependent pathways in A549 lung epithelial cells and B16F10 melanoma cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The application of fluorescence imaging in living cells by confocal laser scanning microscopy and recently by two-photon imaging microscopy can monitor the dynamic aspects of cellular trafficking and colocalization of dendrimers with high spatial and temporal resolution. [23][24][25] The cellular internalization and trafficking of dendrimers depend on their size, shape, charge, and surface functionality as well as the cell type. 26,27 Many studies have revealed that cationic PAMAM dendrimers can cross cell membranes by various endocytic pathways, including clathrin-dependent pathways in Caco-2 cells, 28,29 clathrin-dependent and macropinocytosis pathways in HeLa cells, 30 and non-clathrin, non-caveolae, cholesterol-dependent pathways in A549 lung epithelial cells and B16F10 melanoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…No entry of FITC-G4 PAMAM into human keratinocyte HaCaT cell nuclei was observed after 24 hours and 48 hours treatments by Pai et al, 59 or after 24 hours in primary neuronal cultures. 25 The localization of later generation G6 PAMAM dendrimers conjugated with estrogen was observed in the membrane and cytoplasm, but not in the nuclei of estrogen receptor-positive MCF-7 human breast cancer cells. 66 At the nondividing phase, the nuclear envelope acts as a molecular permeability barrier, enabling the free diffusion of small hydrophilic molecules (up to 9 nm size) through the nuclear pore complex.…”
mentioning
confidence: 95%
“…In vitro studies have revealed that these nanoparticles possess the ability to inhibit the fibrillation and aggregation of proteins involved in neurodegenerative disorders [7][8][9]. Importantly, in vivo studies of polyamidoamine (PAMAM) dendrimers have been performed to determine their toxicity to the central nervous system [10], check their ability to localize in inflammatory cells in the brain [11], and show their potential in dendrimer-drug conjugates for the treatment of neuroinflammation [12,13]. Significant progress has been made in research on the interactions between dendrimers and living cells or organisms, resulting in commercially available products such as transfection agents (SuperFect from Qiagen and PrioFect from EMD-Merck), markers for rapid heart attack diagnosis (Stratus CS Acute Care from Siemens Healthcare), and anthrax-detecting agents (Alert Ticket from the US Army Research Laboratory) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Polyamidoamine (PAMAM) dendrimers have also been used for multivalent display, for example, of siallyllactose21 showing in vitro inhibition at micromolar ligand concentrations as well as protection of mice from infection. However, depending on their structure multivalent PAMAM scaffolds may also be cytotoxic 17, 22, 23…”
mentioning
confidence: 99%